2020
DOI: 10.3389/fgene.2019.01270
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetics and In Utero Acquired Predisposition to Metabolic Disease

Abstract: Epidemiological evidence has shown an association between prenatal malnutrition and a higher risk of developing metabolic disease in adult life. An inadequate intrauterine milieu affects both growth and development, leading to a permanent programming of endocrine and metabolic functions. Programming may be due to the epigenetic modification of genes implicated in the regulation of key metabolic mechanisms, including DNA methylation, histone modifications, and microRNAs (miRNAs). The expression of miRNAs in org… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 107 publications
0
22
0
Order By: Relevance
“…The intrauterine programming of obesity and associated metabolic risks in offspring adulthood rely on epigenetic regulation as one of the key underlying mechanisms (Elshenawy and Simmons, 2016). Epigenetic modifications induced by maternal obesity (MO) (Deodati et al, 2019; Liang et al, 2016) lead to a cyclical transgenerational transmission of obesity that, in the near future, may become a heavy burden worldwide (Iozzo et al, 2014). Therefore, understanding the link between MO and offspring health would allow to anticipate better public health policy and implement more effective interventions.…”
Section: Introductionmentioning
confidence: 99%
“…The intrauterine programming of obesity and associated metabolic risks in offspring adulthood rely on epigenetic regulation as one of the key underlying mechanisms (Elshenawy and Simmons, 2016). Epigenetic modifications induced by maternal obesity (MO) (Deodati et al, 2019; Liang et al, 2016) lead to a cyclical transgenerational transmission of obesity that, in the near future, may become a heavy burden worldwide (Iozzo et al, 2014). Therefore, understanding the link between MO and offspring health would allow to anticipate better public health policy and implement more effective interventions.…”
Section: Introductionmentioning
confidence: 99%
“…Wake-Buck et al identified the VA curvature and orientation at the two vertebral arteries’ confluence as important factors affecting blood flow velocities based on computational fluid dynamics modeling [ 3 ]. In utero factors such as differences in placentation or maternal (external) effects may also influence intrauterine neurogenesis, which may affect cerebral vascular development at the epigenetic level [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Induction of dermal deletion in Dicer or Drosha in the skin of mice after birth also demonstrated the important role of miR-NAs in maintaining the normal process of growth cycle and differentiation of HFSc [13]. More importantly, emerging evidence now supports the idea that DNA methylation is crucially involved in the dysregulation of miRNAs in many diseases, such as cancers, metabolic disorders, and atherosclerosis [14][15][16]. Of note, short interfering RNA (siRNA)-mediated knockdown of DNMT1 has been indicated to restore the expression of miR-214 in testicular germ cell tumor [17].…”
Section: Introductionmentioning
confidence: 90%